Changes in iron status are related to changes in brain activity and behavior in Rwandan female university students: Results from a randomized controlled efficacy trial involving iron-biofortified beans - Wenger, Michael J.; Rhoten, Stephanie E.; Murray-Kolb, Laura E.; Scott, Samuel P.; Boy, Erick; Gahutu, Jean-Bosco; Haas, Jere D. (American Society for Nutrition, 2019)
Background: Evidence suggests that iron deficiency (ID) affects cognitive performance, as measured in behavior. Although such effects must be mediated by changes in the brain, very few studies have included measures of brain activity to assess this relation. Objective: We tested the hypothesis that provision of iron-biofortified beans would result in improvements in measures of iron status, brain dynamics, and behavior.